2018
DOI: 10.1016/j.yfrne.2018.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Sex-related responses after traumatic brain injury: Considerations for preclinical modeling

Abstract: Traumatic brain injury (TBI) has historically been viewed as a primarily male problem, since men are more likely to experience a TBI because of more frequent participation in activities that increase risk of head injuries. This male bias is also reflected in preclinical research where mostly male animals have been used in basic and translational science. However, with an aging population in which TBI incidence is increasingly sex-independent due to falls, and increasing female participation in high-risk activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
98
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(105 citation statements)
references
References 184 publications
(428 reference statements)
3
98
2
2
Order By: Relevance
“…The onset of WM volume changes may be occurring outside of the critical period in female subjects allowing appropriate compensation for early damage . In addition, estrogen and progestogen in females play a critical neuroprotective function in response to stroke, chronic hypoxia and traumatic brain injury in adulthood . Stroke epidemiology indicates that first stroke occur earlier and are more common in men worldwide .…”
Section: Discussionmentioning
confidence: 99%
“…The onset of WM volume changes may be occurring outside of the critical period in female subjects allowing appropriate compensation for early damage . In addition, estrogen and progestogen in females play a critical neuroprotective function in response to stroke, chronic hypoxia and traumatic brain injury in adulthood . Stroke epidemiology indicates that first stroke occur earlier and are more common in men worldwide .…”
Section: Discussionmentioning
confidence: 99%
“…; Späni et al . ). This study examined whether perioperative administration of the sex steroid synthesis inhibitors LET and FIN alter histopathological, neurological, or molecular parameters after experimental TBI using the CCI model.…”
Section: Discussionmentioning
confidence: 97%
“…; Späni et al . ). Systemic application of 17β‐estradiol (E2), the most prevalent and potent estrogen, is beneficial after TBI both in male and female rats (Soustiel et al .…”
mentioning
confidence: 97%
“…Common neurological disturbances accompanying mTBIs range from acute symptoms including headache, nausea, dizziness, light/noise sensitivity, attention, concentration, and memory, to more long-term symptoms including irritability, sleep disturbances, anxiety, and depression [ 17 19 ]. When accounting for all acquired brain injuries, it appears that males experience more mTBIs than females with apparent sexually dimorphic symptomologies [ 20 ]. For example, when comparing male and female concussed soccer players, Covassin and colleagues found that females performed worse in visual memory tasks, had more total concussive symptoms (verbal and visual memory), and higher rates of migraine-induced cognitive fatigue and sleep disturbances up to 8 days post-injury [ 21 ].…”
Section: Traumatic Brain Injurymentioning
confidence: 99%